Added value of combining methotrexate with a biological agent compared to biological monotherapy in rheumatoid arthritis patients: A systematic review and meta-analysis of randomised trials - Tarp, S; Jørgensen, TS; Furst, DE; Dossing, A; Taylor, PC; Choy, EH; Suarez-Almazor, ME; Lyddiatt, A; Kristensen, LE; Bliddal, H; Christensen, R (Elsevier, 2018)
Objectives: To assess the efficacy and safety of methotrexate (MTX) in combination with an approved biological agent compared to biological monotherapy, in the management of patients with rheumatoid arthritis (RA). Methods: MEDLINE, EMBASE, CENTRAL and other sources were searched for randomised trials evaluating a biological agent plus MTX versus the same biological agent in monotherapy. Co-primary outcomes were ACR50 and the number of patients who discontinued due to adverse events (AEs). Random-effects models were applied for meta-analyses with risk ratio and 95% confidence intervals and the GRADE approach was used to assess confidence in the estimates. Results: The analysis comprised 16 trials (4965 patients), including all biological agents approved for RA except anakinra and certolizumab. The overall likelihood of responding to therapy (i.e. ACR50) after 6 months was 32% better when MTX was given concomitantly with biological agents (1.32 [1.20–1.45]; P ≺ 0.001) corresponding to 11 more out of 100 patients (7–16 more); Moderate Quality Evidence. Discontinuing due to AEs from concomitant use of MTX was potentially 20% increased (1.21 [0.97–1.50]; P = 0.09) compared to biological monotherapy corresponding to 1 more out of 100 patients (0–3 more); Moderate Quality Evidence. Conclusions: Randomised trials provide Moderate Quality Evidence for a favourable benefit-harm balance supporting concomitant use of MTX rather than monotherapy when prescribing a biological agent in patients with RA although in absolute terms only 7–16 more out of 100 patients will achieve an ACR50 response after 6 months of this combination therapy.